INNOVATION AND TECHNOLOGY IN RURAL ECONOMIC DEVELOPMENT: A LITERATURE REVIEW OF GLOBAL PRACTICES - Zeni Zainal Muis; Dina Octaviani; Sigit Sugiardi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This article examines the role of innovation and technology in rural economic development through a literature review of global practices. It is found that digital technologies, precision agriculture and renewable energy contribute significantly to increased productivity, efficiency and sustainability in rural areas. Conducive government and policy support is also needed to encourage technology adoption through investments in infrastructure, technical training and access to finance. In addition, participatory approaches involving local communities are strongly encouraged to ensure innovations are appropriate to local needs and culture. With that, the importance of innovation and technology in empowering rural communities and reducing economic disparities between urban and rural areas.